Сезонное распределение радиолокационных характеристик облачности при шквалах на юго-востоке Западной Сибири (Географический вестник=Geographical bulletin, 2017)
Рассмотрено изменение радиолокационных характеристик конвективной облачности при шквалах в течение тёплого сезона года. Определены средние статистические значения данных характеристик для юго-востока Западной Сибири. Полученные результаты позволят уточнить существующие методы прогноза шквалов.THE SEASONAL DISTRIBUTION THE RADAR CHARACTERISTICS OF SQUALLS IN A SOUTHEAST OF WESTERN SIBERIAChanges the radar characteristics of convective cloud of squalls during warm seasons of year are discussed. Middle statistical values of radar characteristics for southeast of Western Siberia are presented. The results will allow methods of the forecast of squalls to improve.